Organizing Canadian Theatre Designers: The Intersection of Creative and Precarious Labour - Moore, Conor (Simon Fraser University, 2020)
Canadian theatre designers share many similarities with other freelance, creative workers in Canada. The conditions of precarity that define their working relationships are similar to those that affect workers in other sectors, such as film, music, television, and visual arts. This thesis begins by examining the existing literatures and research concerning creative and precarious work, primarily in Canada, but also internationally. Drawing on in-depth interviews of 55 designers from within the relatively small community of Canadian theatre designers, approximately 500-700 workers, I examine the working conditions that designers find challenging and seek suggestions for how they can be improved. Additionally, I explore the different models that designers have used to organize in Canada, Quebec, and the United States. By comparing these models with the interviews from designers, I conclude that the best way for Canadian designers to improve their working conditions is to build a closer relationship with IATSE [International Alliance of Theatrical Stage Employees], the union that represents stagehands and technicians. Finally, I identify some questions for further exploration, including the tension between artistic and worker identities, while also touching on the present circumstances of the Covid-19 crisis and the current conversations concerning racism and white supremacy within Canadian society.